PENERAPAN COMMUNITY BASED TOURISM DALAM PENGELOLAAN POTENSI WISATA BAHARI SECARA BERKELANJUTAN DI KABUPATEN PANGANDARAN - Ade Tri Putra; Djoko S. Abi Suroso (Journal of Tourism Destination and Attraction, 2023)
Marine tourism holds important benefits for the environment and socio-economics of the people who live surrounding. In this condition, it is necessary to realize the importance of managing marine tourism in Indonesia Pangandaran Regency. Several tourist objects in Pangandaran Regency were damaged due to the lack of management due to the lack of attention of stakeholders in tourist objects. This has an impact on reducing the number of tourist visits. In this case it is necessary. implementation on an ongoing basis which aims to support efforts to maintain and preserve conservation areas through marine nature tourism activities by paying attention to educational elements and increasing the level of local communities in prioritizing economic, social, cultural, and political principles environment. The author finds out the parameters of Coastal Tourism with Community. Based principles Tourism in a sustainable manner in managing marine tourism destinations in Pangandaran Regency, which will lead to community participation in managing the potential of natural resources optimal of the parameters studied using the relevant concepts from World Tourism. Organization, then the writer analyzes the causal framework to describe the interaction. between society and the environment or vice versa because of interdependence, by using DPSIR: Drivers, Pressure, State, Impact and Response.